1994
DOI: 10.1021/om00022a031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Crystal Structures of Monomeric and Dimeric Palladium(II) Amide Complexes

Abstract: Addition of KN(R)Ph to írans-CPMeskPdCR')! (R = H, Me; R' = Ph, Me) results in the formation of the monomeric anilide complexes ircms-CPMeghPdCRONCRiPh in good yield. A single-crystal X-ray diffraction study of #rans-(PMe3)2Pd(Ph)N(H)Ph (1) reveals that it crystallizes in the space group PI with a = 8.423(3) Á, h = 10.768(4) Á, c = 12.565 Á, a = 68.81(3)°, ß -71.90(3)°, y = 87.65(3)°, V -1006.7(7) Á3, and Z = 2. There is no evidence for significant interaction between the N lone pair and the metal center, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 0 publications
3
86
0
1
Order By: Relevance
“…This fact has been reported as transphobia, [14,15] and is followed in trans-[PdAr(NHPh)(PMe 3 ) 2 ]. [8] In complex 1 the hard N(amido) ligand arranges cis to the PdϪC(aryl) bond, leaving the softer ligand chloro in trans position to the PdϪC(aryl) bond. The alternative trans isomer of 1 would contain a PdϪC(aryl) bond with the harder amido ligand in trans position, obeing transphobia arguments, but this isomer is not formed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact has been reported as transphobia, [14,15] and is followed in trans-[PdAr(NHPh)(PMe 3 ) 2 ]. [8] In complex 1 the hard N(amido) ligand arranges cis to the PdϪC(aryl) bond, leaving the softer ligand chloro in trans position to the PdϪC(aryl) bond. The alternative trans isomer of 1 would contain a PdϪC(aryl) bond with the harder amido ligand in trans position, obeing transphobia arguments, but this isomer is not formed.…”
Section: Methodsmentioning
confidence: 99%
“…[6,7] Mononuclear complexes of general formula [PdAr(NHPh)(PMe 3 ) 2 ] with these two bonds in trans array have also been reported. [8] They were stabilized against the natural tendency of terminal PdϪN(amido) bonds to make bridges, by using P-donor ligands cis to the amido bond. The stabilization of palladium compounds containing PdϪC and PdϪN(amido) bonds in a cis disposition has been achieved introducing the P-donor nonlabile chelating ancillary ligand DPPF [1,1Ј-bis(diphenylphosphanyl)ferrocene].…”
Section: Introductionmentioning
confidence: 99%
“…Both Boncella et al [66] and Hartwig et al [63,64,101] have observed these reactions with palladium amido aryl complexes. Hartwig's group has studied the mechanism of this process in detail [101,280].…”
Section: Reductive Eliminations Of Amines From Pd(ii) Amido Complexesmentioning
confidence: 88%
“…Kinetic studies on stoichiometric reactions from isolated amido and alkoxo organopalladium complexes have shed 26 1 Mechanistic Aspects of Metal-Catalyzed C,C-and C,X-Bond-Forming Reactions light into the mechanism by identifying the actual species involved and the factors controlling this process. The most extensively studied of these reactions is the reductive elimination of C-N bonds from amido arylpalladium complexes [215,216]. Both monomeric and dimeric species have been studied.…”
Section: Key Intermediates In the Formation Of C-x (X ¼ N O S) Bondmentioning
confidence: 99%